Teaching across grades: lesson delivery strategies of ESL teachers in multigrade classrooms at selected Malaysian low enrolment schools - Tahir, Nur Anisah; Saad, Mohammad Azannee; Raja Abdul Razak, Raja Nurul Nadia (Global Academic Excellence, 2026)
Multigrade classrooms are a common feature of rural low enrolment schools worldwide, where students from two different grade levels are taught within the same classroom. In the Malaysian context, such settings pose distinct pedagogical demands, particularly for English as a Second Language (ESL) instruction. This study explores the lesson delivery strategies employed by ESL teachers in selected Malaysian low enrolment multigrade schools. Guided by the Learning Environment, Learning Processes, and Learning Outcomes (LEPO) framework, a qualitative case study design was adopted. Data were collected through semi-structured interviews, classroom observations, and document analysis involving eight ESL teachers from selected low enrolment schools in Selangor, Pahang, Perak, and Johor. The findings revealed six main themes; alternating instructional focus between different grade levels, alignment of language skills and topics across grades, peer-assisted learning practices, multigrade lesson planning approaches, utilisation of instructional materials, and, differentiated teaching strategies in multigrade classrooms. These findings offer practical insights into ESL teaching in multigrade settings and have implications for teachers, school leaders, policymakers, and other educational stakeholders seeking to support effective instruction in rural low enrolment schools